Peacebuilding and international administration : the cases of Bosnia and Herzegovina and Kosovo - van Willigen, Niels (2013)
"This book provides a detailed historical and political analysis of the role and effectiveness of international administration in state-building. It analyses how the international administrations in Bosnia and Herzegovina and Kosovo have attempted to create sustainable political institutions and to what extent they have been successful in doing so"--
Includes bibliographical references and index.
Keywords: International agencies -- Bosnia and Hercegovina -- Politics and government; International agencies -- Kosovo (Republic); POLITICAL SCIENCE / General; Bosnia and Hercegovina -- Politics and government; Kosovo (Republic) -- Politics and government